Deep infection after hip hemiarthroplasty: risk factors for infection and outcome of treatments. (18th November 2021) - Craxford, Simon; Marson, Ben A.; Nightingale, Jessica; Ikram, Adeel; Agrawal, Yuvraj; Deakin, Dan; Ollivere, Benjamin
Abstract : Aims: Deep surgical site infection (SSI) remains an unsolved problem after hip fracture. Debridement, antibiotic, and implant retention (DAIR) has become a mainstream treatment in elective periprosthetic joint infection; however, evidence for DAIR after infected hip hemiarthroplaty is limited. Methods: Patients who underwent a hemiarthroplasty between March 2007 and August 2018 were reviewed. Multivariable binary logistic regression was performed to identify and adjust for risk factors for SSI, and to identify factors predicting a successful DAIR at one year. Results: A total of 3, 966 patients were identified. The overall rate of SSI was 1.7% (51 patients (1.3%) with deep SSI, and 18 (0.45%) with superficial SSI). In all, 50 patients underwent revision surgery for infection (43 with DAIR, and seven with excision arthroplasty). After adjustment for other variables, only concurrent urinary tract infection (odds ratio (OR) 2.78, 95% confidence interval (CI) 1.57 to 4.92; p < 0.001) and increasing delay to theatre for treatment of the fracture (OR 1.31 per day, 95% CI 1.12 to 1.52; p < 0.001) were predictors of developing a SSI, while a cemented arthroplasty was protective (OR 0.54, 95% CI 0.31 to 0.96; p = 0.031). In all, nine patients (20.9%) were alive at one year with a functioning hemiarthroplasty following DAIR, 20 (46.5%) required multiple surgical debridements after an initial DAIR, and 18 were converted to an excision arthroplasty due to persistent infection, with six were alive at one year. The culture of any gram-negative organism reduced success rates to 12.5% (no cases were successful with methicillin-resistant Staphylococcus aureus or Pseudomonas infection). Favourable organisms included Citrobacter and Proteus (100% cure rate). The all-cause mortality at one year after deep SSI was 55.87% versus 24.9% without deep infection. Conclusion: Deep infection remains a devastating complication regardless of the treatment strategy employed. Success rates of DAIR are poor compared to total hip arthroplasty, and should be reserved for favourable organisms in patients able to tolerate multiple surgical procedures. Cite this article: Bone Jt Open  2021;2(11):958–965.